2019
DOI: 10.1088/1748-605x/ab4fb5
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration of preosteoblast cells on a clinical gelatin sponge for 3D bone tissue engineering

Abstract: Using three-dimensional (3D) bone engineering to fabricate bone segments is a better choice for repairing bone defects than using autologous bone. However, biomaterials for bone engineering are burdened with some clinical safety concerns. In this study, we layered commonly found clinical materials, hemostatic gelatin sponges, in a novel manner to create a 3D scaffold for bone engineering purposes. We further examined the comparable benefits of our design with both closed- and open-bottom holders. Cells in stac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…Since a single scaffold (1 mm) is not thin enough for nutrient and oxygen diffusion, after multilayered construction, an oxygen gradient within 5-layered gelatine sponge was obviously formed and cell behaviours (including cell viability and gene expression profile) were changed inside the construct. In a previous study, aerobic pre-osteoblast cells cultured on the bottom layer migrated to the top layer (Wang et al, 2019). However, low-oxygenrequiring NP cells would migrate to the bottom layer (data not shown).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Since a single scaffold (1 mm) is not thin enough for nutrient and oxygen diffusion, after multilayered construction, an oxygen gradient within 5-layered gelatine sponge was obviously formed and cell behaviours (including cell viability and gene expression profile) were changed inside the construct. In a previous study, aerobic pre-osteoblast cells cultured on the bottom layer migrated to the top layer (Wang et al, 2019). However, low-oxygenrequiring NP cells would migrate to the bottom layer (data not shown).…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies have shown that gradients of oxygen and nutrient concentrations exist within a 3D multilayered culture, similar to the microenvironmental changes observed during NP degeneration (Bettahalli al., 2014;Derda et al, 2009;Wang et al, 2019). It has not been shown whether the 3D multilayered culture model can mimic the progress of NPD.…”
Section: Discussionmentioning
confidence: 99%
“…Preosteoblasts were observed to form cell bridges between adjacent rods by employing the long filopodia and sheet-like lamellipodia (Figure ). In contrast to the limited preosteoblast migration to the bottom of the multilayered scaffolds, preosteoblasts in the nanoapatite-PMDE-scaffold showed autonomous cell migration from the top to the bottom. This phenomenon suggested that the mass transport of oxygen and nutrients within the nanoapatite-PMDE-scaffold was efficient to support the cellular activities of preosteoblasts, which resulted in high levels of oxygen and nutrients throughout the scaffold instead of being restricted at the top .…”
Section: Resultsmentioning
confidence: 76%
“…The preosteoblasts were preferentially aligned along the rods, suggesting that the cells were able to recognize the biophysical cues in the microenvironment and coordinate their behaviors. Substrate anisotropy provides an important cue to direct cellular orientation, , and preosteoblasts were reported to align along the fibers in polystyrene scaffolds coated with growth factors . In the nanoapatite-PMDE-scaffold, the combination of rod alignment with the polyelectrolyte and nanoapatite modification provides an effective approach to spatially control cell alignment and proliferation without involving growth factors.…”
Section: Resultsmentioning
confidence: 99%
“…Since we also noticed fewer cells in the central area of GH than in GH+PEG, we next examined if cell migration is one mechanism resulting in the difference in GAG deposition. Previously, it had been reported that MSCs could migrate in hyaluronic acid [ 19 ] and gelatin [ 20 ]-based scaffolds. However, in the method that we used in this study to assess cell migration, we did not see MSCs that crossed from ring to disc or vice versa.…”
Section: Discussionmentioning
confidence: 99%